Comparison of swept-source and enhanced depth imaging spectral-domain optical coherence tomography in quantitative characterisation of the optic nerve head - Li, Dejiao; Taniguchi, Elise V; Cai, Sophie; Paschalis, Eleftherios I; Wang, Haobing; Miller, John B; Turalba, Angela V; Greenstein, Scott H; Brauner, Stacey; Pasquale, Louis R; Shen, Lucy Q (British journal of ophthalmology, 2017)
To compare swept-source optical coherence tomography (SS-OCT) and enhanced depth imaging spectral-domain OCT (EDI-OCT) in quantitative assessment of optic nerve head (ONH) parameters. In a cross-sectional study, patients with primary open angle glaucoma (POAG) and age-matched control subjects underwent SS-OCT and EDI-OCT B-scans of the ONH in a single visit. Two masked readers independently measured the horizontal and vertical lamina cribrosa depth (LCDH and LCDV, respectively), as well as thinnest Bruch's membrane opening minimum rim width (BMO-MRW) from SS-OCT and EDI-OCT scans. We assessed agreement between SS-OCT and EDI-OCT measurements by linear regression models, Bland-Altman analysis and concordance correlation coefficients (CCC). Intrareader and inter-reader reproducibility was assessed using intraclass correlation coefficients (ICC). One eye from each of 40 patients with POAG and 20 controls were included. All three ONH measurements were higher on SS-OCT than on EDI-OCT, with significant differences in LCDH (mean difference=31.7 µm, p<0.01) and thinnest BMO-MRW (mean difference=20.5 µm, p<0.01). Linear regression models described the agreement between SS-OCT and EDI-OCT measurements with R >0.8 for LCDH among both patients with POAG and controls and for thinnest BMO-MRW among patients with POAG. The CCC was >0.8 overall for each parameter. Intrareader and inter-reader ICCs were ≥0.989 and ≥0.964, respectively, for all parameters. LCDH, LCDV and thinnest BMO-MRW measurements are not interchangeable between SS-OCT and EDI-OCT, but show good intrareader and inter-reader reproducibility and interdevice agreement for quantitative characterisation of the ONH, particularly among patients with glaucoma.